Copper strontium phosphate glasses with high antimicrobial efficacy - Roman Golovchak; Bohdan Mahlovanyi; Yaroslav Shpotyuk; Malgorzata Kus-Liskiewicz; Julia Kozianska; Renata Zadrag-Tecza; Grzegorz Zagula; Malgorzata Trzyna-Sowa; Andriy Kovalskiy; Agnieszka Gala-Bladzinska; Jozef Cebulski (Scientific Reports)
Abstract The emergence of antibiotic-resistant strains caused by the extensive use of antibiotics in the world requires a preventive approach to stop the infection spread, especially in a hospital setting. So, there is a growing demand for materials that can inhibit bacteria growth or have bactericidal effects. In this paper, an inexpensive and durable Cu-containing strontium-modified phosphate glass with a considerable antimicrobial effect is proposed. The basic physical properties of the material are studied, and its antimicrobial effect is evaluated on Staphylococcus aureus bacteria, known to be the most common problem in hospital environments because of healthcare-associated infections. The glass powders demonstrate strong antibacterial efficacy with a concentration of only a few mg/mL, sufficient to eradicate the entire bacterial colonies within 24 h. Bulk surfaces of these glasses inhibit bacterial growth and release low, non-toxic levels of their constituent elements into simulated body fluid. On the basis of the obtained results, it is shown that the proposed glass can be used as a structural material for various medical equipment and/or components of antimicrobial coating/paint not only in medicine but also for high touch point articles in public places like schools, gyms, public offices and similar.